2021
DOI: 10.3390/brainsci11070833
|View full text |Cite
|
Sign up to set email alerts
|

Acute MPTP Treatment Impairs Dendritic Spine Density in the Mouse Hippocampus

Abstract: Among the animal models of Parkinson’s disease (PD), the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-lesioned mouse model has shown both dopaminergic (DA) damage and related motor control defects, as observed in patients with PD. Recent studies have suggested that the DA system interacts with the synaptic plasticity of the hippocampus in PD. However, little is known about how alterations in the hippocampal structural plasticity are affected by the DA damage in MPTP-lesioned models. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Collectively, our findings correspond to previous studies and anticipation (Villalba et al., 2009; Weerasinghe‐Mudiyanselage et al., 2021). The PD model has been successfully established in mice (Jenner, 2003); hence, determining the dendritic spine density of striatal MSNs and expression of SNK and SPAR can afford valuable insights.…”
Section: Discussionsupporting
confidence: 93%
“…Collectively, our findings correspond to previous studies and anticipation (Villalba et al., 2009; Weerasinghe‐Mudiyanselage et al., 2021). The PD model has been successfully established in mice (Jenner, 2003); hence, determining the dendritic spine density of striatal MSNs and expression of SNK and SPAR can afford valuable insights.…”
Section: Discussionsupporting
confidence: 93%
“…Structural plasticity in the hippocampus can be influenced by a variety of stimuli, some of which appear to have long-term effects [ 8 ]. Previous studies found that dendritic complexity and/or spine density was altered in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-lesioned [ 17 , 18 ] and leucine-rich repeat kinase 2-mutant mouse PD models [ 19 , 20 ]. However, many questions remain unanswered about the functional and structural changes of hippocampal neurons that occur in PD.…”
Section: Introductionmentioning
confidence: 99%
“…Spine density in the hippocampal DG region was decreased in MPTP-lesioned mice along with a remarkable decrease in the proteins that mediated neuroplasticity mechanisms and impaired cognitive function [ 139 ]. Similarly, a recent study found decreased spine density in both CA1 and DG subregions of the MPTP-lesioned mice during the late phase of PD [ 289 ]. In LRRK2-mutant mice, newly generated DG neurons were found with reduced dendritic spines [ 288 ].…”
Section: Hippocampal Structural Plasticity In Neurodegenerative Diseasesmentioning
confidence: 74%
“…Dendritic length and branching were reduced in primary cultured hippocampal neurons [ 286 ] and newly generated DG neurons [ 287 , 288 ] in the LRRK2-mutant mice. However, a previous study showed that the dendritic complexity of both CA1 and DG subregions was not altered in the MPTP-lesioned mice [ 289 ]. Therefore, further studies are needed to confirm dendritic pathology in PD animal models, since variations in observations due to different models cannot be neglected.…”
Section: Hippocampal Structural Plasticity In Neurodegenerative Diseasesmentioning
confidence: 99%